Relationships between coordination, strength and performance during initial sprint acceleration - Donaldson, B.; Bezodis, N.; Bayne, H. (Journal of Sports Sciences, 2025)
Despite strong logical and theoretical links, no studies have directly examined the relationship between physical qualities and coordination during sprint acceleration. The aim of this study was to assess the associations between initial acceleration coordination and lower body strength and explore potential interactions between strength and coordination in relation to acceleration performance. Sagittal plane kinematics and velocity-time profiles were obtained for highly trained to world class male sprinters (100 m PB: 9.95-11.17 s). Thigh-thigh and shank-foot coordination was determined for the first four steps using vector coding, and external kinetic parameters derived from a mono-exponential fit to velocity-time profiles. Lower body strength was measured with isometric squat (ISqT), countermovement jump (CMJ), repeated hop (HJ) and Nordic hamstring tests. Large to very large correlations (rho = 0.59-0.82) existed between ISqT, CMJ, HJ tests and specific coordination features in both step 1 and steps 2-4, and exploratory regression analyses suggested the potential for higher or lower magnitudes of a given strength capacity to modify the relationships between coordination features and acceleration performance. These findings support an individualised approach to technique in sprint training, and consideration of the influence of strength qualities on the adoption and effectiveness of particular movement patterns.